1972
DOI: 10.1042/bj1281221
|View full text |Cite
|
Sign up to set email alerts
|

The formation of pyrrolid-2-one-5-carboxylic acid at the N-terminus of immunoglobulin G heavy chain

Abstract: We propose that pyrrolid-2-one-5-carboxyl-tRNA is not involved in the initiation of protein synthesis in eukaryotic cells and that the N-terminal pyrrolid-2-one-5-carboxylic acid group of an IgG (immunoglobulin G) (that secreted by the mouse plasmacytoma Adj PC5) is formed by the enzymic cyclization of the N-terminal glutamine of the heavy chain of the completed IgG molecule and that the cyclization takes place inside the cell. We base these conclusions on the following evidence. (1) Pyrrolidonecarboxyl-tRNA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1972
1972
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 30 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Purification of intracellular and secreted Adj PC5 IgG: chain separation. The purification of 3H-labelled intracellular IgG and "4C-labelled secreted IgG, separation of heavy chains and light chains and measurement of the 3H/14C ratios of the chains have been fully described by Stott & Munro (1972).…”
Section: Methodsmentioning
confidence: 99%
“…Purification of intracellular and secreted Adj PC5 IgG: chain separation. The purification of 3H-labelled intracellular IgG and "4C-labelled secreted IgG, separation of heavy chains and light chains and measurement of the 3H/14C ratios of the chains have been fully described by Stott & Munro (1972).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of monoclonal antibodies have only one N-linked glycosylation site in the constant region of each heavy chain (Takahashi et al, 1987), but N-linked glycosylation in the Fab region has also been observed (Rudd et al, 1991;Endo et al, 1995). In addition to N-linked glycosylation, monoclonal antibodies can have a number of common PTMs such as: processing of the C-terminal Lys on the heavy chain (Harris, 1995), Met oxidation (Shen et al, 1996), Trp oxidation (Matamoros Fernandez et al, 2001), fragmentation in the hinge region (Cordoba et al, 2005), glycation (Lapolla et al, 1997;Harris, 2005), Asp isomerization (Cacia et al, 1996), Asn deamidation (Perkins et al, 2000;Harris et al, 2001), N-terminal pyroglutamic acid formation (Stott & Munro, 1972;Burstein, Kantour, & Schechter, 1976;Rose et al, 1984;Chelius et al, 2006;Yu et al, 2006), cysteinylation (Gadgil et al, 2006), and, in one case, a thioether linkage between the light chain and heavy chain (Tous et al, 2005). Thus, a monoclonal antibody is a heterogeneous molecule and must be characterized extensively before therapeutic use in humans.…”
Section: B Monoclonal Antibody Sequence and Structural Characterizatmentioning
confidence: 99%
“…These data suggest that the blocked 5563 H chain belongs to a previously undescribed VH subgroup containing a phenylalanine at position 5 , a proline at position 7 and an unknown, subgroup-determining residue at position 10 of the mature H chain. Whether this subgroup is peculiar to either the C 3 H mouse or to blocked H chains is not known; the sequences of few C 3 H Ig and only the N-terminal tetrapeptide of one blocked mouse H chain (AdjPc5; PCA-Val-Gln-Leu; [17]) have been reported.…”
mentioning
confidence: 99%